Analisis Faktor-Faktor Yang Mempengaruhi Minat Pemain Dalam Permainan AR Berbasis Lokasi (Studi Kasus Pokemon GO) - Kevin Dwiki Saputra; Hanifah Muslimah Az-Zahra; Aryo Pinandito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Pokemon GO is a location-based game with Augmented Reality (AR) technology. This game had 1,600,000 daily players on July 2016 and retain this number until 3 following months. This game also held 5 records in Guinness World Record on many aspects. But, as the time goes, Pokemon GO players keep declining until there are only 148,000 daily players on January 2017 and still retain this number until June 2017. To uncover the reasons why the number of Pokemon GO players keep declining, collecting data of 2 groups of player is needed, one with low-level players (level 3-15) and one with high-level players (above level 15) so it can be analyzed. There are 2 main methods for collecting data, the first is with questionnaire and the second is with interviews. These two methods will mainly based around game-design factors (Yen-Ru Shi and Ju-Ling Shih, 2015). After collecting data, the analysis process will determine whether there are significant differences among values and how questionnaires data and interviews data are related so conclusion can be made on why players left Pokemon GO. Lastly, recommendation will be made so this game and games with similiar type can meet the expectation of the players.